Orange albedo flour as a fat replacer in beef burgers: adding value to citrus industry by-products (Research, Society and Development, 2020)
Dietary fiber is an important component to improve the nutritional appeal of meat products, and it could be obtained from by-products of the citrus industry. Considering that orange albedo was not sufficiently addressed in meat products, the purpose of this work was to evaluate the influence of the orange albedo flour as an animal fat substitute in beef burgers. Five formulations were developed with different substitutions of pork fat by the orange albedo flour (0; 25; 50; 75; and 100%). The analyses carried out were the proximal composition of orange albedo flour and beef burgers and the cooking yield, shrinkage, pH, color, sensory acceptance, and purchase intent of the beef burgers. The results showed that the percentage of lipids was reduced by up to 70%, however, the yield parameters were negatively affected by the inclusion of the orange albedo flour: the higher the amount of flour added, lower was the water retention capacity and higher was the shrinkage rate. Concerning sensory analysis, the formulations that pork back fat was substituted by 25 and 50% of orange albedo flour were the most acceptable for all sensory attributes and purchase intention, characterizing themselves as viable alternatives both of the nutritional and sensory aspects.